Sirtuins as a potential molecular target of cosmetic ingredients - Katarzyna Brezdeń; Katarzyna Pańczyk-Straszak; Anna Waszkielewicz (Polish Pharmaceutical Society, 2022)
Sirtuins are a group of enzymes belonging to histone deacetylases. However, they can also catalyze other deacylation reactions (including, for example, demallonylation, desuccinylation or deglutarylation), as well as ADP-ribosylation reactions. In addition to lysine residues localized within histones, a number of other proteins may also be the substrates of the enzymatic reactions catalyzed by sirtuins (including, among others, proteins involved in metabolic processes, the redox balance maintenance or the repair of genetic material). Among mammalian sirtuins, there are seven isoforms: SIRT1-SIRT7, differentiated in terms of localization, catalyzed types of reactions and protein substrates. SIRT1 and SIRT2 are located in the cytoplasm and cell nucleus, SIRT3, SIRT4 and SIRT5 are so-called mitochondrial sirtuins, SIRT6 is present in the nucleus and SIRT7 in the nucleolus. Sirtuins are an interesting molecular target, among others, in the context of cancer therapy and neurodegenerative diseases. In recent years, the issue of the potential use of sirtuin modulators has also been discussed in the cosmetics industry. Numerous studies prove the great importance of the activity of particular types of sirtuins in the processes taking place within the skin. These include processes related to intrinsic and extrinsic aging (primarily related to the harmful effects of UV radiation), proliferation and differentiation of keratinocytes, as well as processes taking place within the hair follicles and hair. At the molecular level, the participation of sirtuins is important, among others. in the regulation of metabolism, apoptosis and redox processes. Currently, the cosmetics industry uses active substances that increase the activity of sirtuins, e.g. resveratrol, astaxanthin, selected fatty acids, quercetin, luteolin, biopeptides obtained from Kluyveromyces yeast and ascorbyl glucoside. In most cases, however, sirtuin modulation is not the primary mechanism of action of these compounds. Another frequently used cosmetic ingredient is one of the sirtuin inhibitors - nicotinamide (niacinamide). However, the importance of this activity for its function in cosmetic products is still debatable. The sirtuin diet has also been gaining popularity in recent years. The so-called 'sirtfood' increases the activity of sirtuins and in this way may contribute to lifespan prolongation or obesity treatment.